Pengaruh Pendapatan dan Toleransi Risiko terhadap Keputusan Investasi pada Karyawan Generasi Z di Jakarta Pusat dengan Kontrol Diri sebagai Variabel Moderasi - Ariani Eka Artanti; Saparuddin Saparuddin; Herlitah Herlitah (Indo Publishing, 2026)
This study aims to analyze the influence of income and risk tolerance on investment decisions among Generation Z employees in Central Jakarta, with self-control as a moderating variable. This research uses a quantitative approach with an associative causal design. The sample consists of 135 Generation Z employees selected using purposive sampling. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The results show that income has a positive and significant effect on investment decisions (β = 0.368; T = 9.274; p = 0.000), and risk tolerance also has a positive and significant effect on investment decisions (β = 0.244; T = 5.871; p = 0.000). Self-control moderates the effect of income on investment decisions positively and significantly (β = 0.144; T = 4.202; p = 0.000), and also moderates the effect of risk tolerance on investment decisions positively and significantly (β = 0.161; T = 4.198; p = 0.000). The R-Square value of 0.873 indicates that all variables explain 87.3% of investment decisions. These findings confirm that income and risk tolerance are important factors, while self-control strengthens their influence on investment decisions.